2017
DOI: 10.1007/s00248-017-0996-9
|View full text |Cite
|
Sign up to set email alerts
|

An 18S rRNA Workflow for Characterizing Protists in Sewage, with a Focus on Zoonotic Trichomonads

Abstract: Microbial eukaryotes (protists) are important components of terrestrial and aquatic environments, as well as animal and human microbiomes. Their relationships with metazoa range from mutualistic to parasitic and zoonotic (i.e., transmissible between humans and animals). Despite their ecological importance, our knowledge of protists in urban environments lags behind that of bacteria, largely due to a lack of experimentally validated high-throughput protocols that produce accurate estimates of protist diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 57 publications
1
32
0
1
Order By: Relevance
“…Although the average values are not significantly different from each other (t-test, p = 0.752), the average Shannon diversity and inverse Simpson indexes for V4 region is slightly higher than those for the V9 region. Several previous studies reported that the Shannon diversity and inverse Simpson indexes for V4 region were lower than those for V9 region 20,21,33 . Conversely, Hirakata et al 30 reported that the Shannon diversity and inverse Simpson indexes for V4 region were higher than those for the V9 region, consistent with our results.…”
Section: Scientific Reports |mentioning
confidence: 77%
See 2 more Smart Citations
“…Although the average values are not significantly different from each other (t-test, p = 0.752), the average Shannon diversity and inverse Simpson indexes for V4 region is slightly higher than those for the V9 region. Several previous studies reported that the Shannon diversity and inverse Simpson indexes for V4 region were lower than those for V9 region 20,21,33 . Conversely, Hirakata et al 30 reported that the Shannon diversity and inverse Simpson indexes for V4 region were higher than those for the V9 region, consistent with our results.…”
Section: Scientific Reports |mentioning
confidence: 77%
“…The determination of the identity threshold is one of the critical steps affecting the number of examined OTUs 21,23 . At the higher identity threshold, the estimation of diversity in eukaryotes is more conservative 13,20 . Surprisingly, Tragin et al 21 and Piredda et al 8 demonstrated that the fraction of the Figure 5.…”
Section: Scientific Reports |mentioning
confidence: 99%
See 1 more Smart Citation
“…Demultiplexed reads were subjected to de novo chimera checking and removal of singletons, and they were clustered into OTUs at 98% identity following the UPARSE pipeline (USEARCH version 8.0.1) ( 86 ). Taxonomy was assigned to representative OTU sequences using BLAST ( 87 ) within QIIME, first against a curated SILVA database ( 88 ) and subsequently with the QIIME-formatted SILVA 111 database clustered at 99% identity ( 89 ). OTUs with no significant hits (<90% identity) after both rounds of taxonomic assignment were labeled as “unidentified.” OTUs were then filtered to remove non-18S rRNA gene sequences (bacterial and archaeal OTUs), host sequences ( B. germanica ), and low-abundance OTUs making up <0.001% of reads in the total data set, as recommended for Illumina sequencing data ( 90 ).…”
Section: Methodsmentioning
confidence: 99%
“…Operational taxonomic unit (OTU) clustering was carried out in this study using a 98% clustering identity threshold that is more stringent than the more commonly used 97% threshold. OTU clustering at 97% has recently been shown to be too conservative for estimating diversity in microbial eukaryotes, merging different species in the same cluster [ 56 , 57 ]. Further, a 97% clustering identity is usually applied to illumina amplicons when targeting variable rRNA regions [ 58 ], with a more stringent threshold being traditionally applied to longer read rRNA amplicons encompassing conserved and variable regions [ 56 , 59 ].…”
Section: Methodsmentioning
confidence: 99%